Meningkatkan Keputusan Pembelian Melalui Influencer dan Sosial Media Instagram Pada Busana Muslim id Maera Indonesia Bandung - Muinah Fadhilah; Agus Dwi Cahya; Pira Maulida (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to examine the influence of influencers and social media in-stagram on increasing purchasing decisions. This type of research is quantitative research. The sample in this study was obtained using purposive sampling method, namely the selection of samples with predetermined criteria. Based on the purposive sampling method, 100 samples were obtained from followers of the Maera Indonesia Instagram account, the data collection method was carried out by distributing questionnaires online with the platform, namely Google Form. The data analysis method used is multiple linear regression using SPSS version 25 program. The results of this study indicate that the influencer variable (X1) has a significant positive effect on purchasing decisions (Y) with a regression coefficient of -0.172 and a sig value of 0.042. social media variable (X2) has a positive and significant effect on purchasing decisions (Y) with the results of the regression coefficient value of 0.312 and a significant value of 0.005 Then the Instagram variable (X3) has a positive and significant effect on purchasing decisions (Y) with the results of the coefficient value regression of 0.315 and a value of 0.004 sig. Keywords: Influencer, Social Media, Instagram, Purchase Decision